Chemistry on the electrodes: post-functionalization and stability enhancement of anchored dyes on mesoporous metal oxide photoelectrochemical cells with copper-free Huisgen cycloaddition reaction. Issue 25 (17th June 2020) - Bentounsi, Yousra; Seintis, Konstantinos; Ameline, Dorine; Diring, Stéphane; Provost, David; Blart, Errol; Pellegrin, Yann; Cossement, Damien; Vauthey, Eric; Odobel, Fabrice
Abstract : Copper-free Huisgen cycloaddition reaction was applied to post grafted dyes on mesoporous electrodes. It enhances the stability towards desorption and offers the possibility of dye functionalization directly performed on the electrodes. Abstract : Hybrid materials consisting of nanocrystalline metal oxide films coated with molecules have considerable implications for the development of optoelectronic devices. We report on a straightforward and versatile procedure to engineer stable layers made of molecules chemisorbed on the surface of mesoporous inorganic metal oxides. The procedure is based on a thermal copper-free Huisgen reaction, which is directly conducted on TiO2 or NiO nanocrystalline films, between already bound diketopyrrolopyrrole sensitizers substituted by two azido groups and a crosslinking agent consisting of a tetrapropiolate ester. The procedure is mild and simple and does not require a catalyst, since quantitative conversion is obtained by a simple heating of the photoelectrode into a solution of the crosslinking agent. The photoelectrodes were characterized by ToF-SIMS, femtosecond transient absorption spectroscopy, electrochemistry and were finally used to fabricate dye-sensitized solar cells with iodide/triiodide and cobalt trisbipyridine complexes as redox mediators. Important increased stability of the crosslinked films was demonstrated by desorption and cyclic voltammetry experiments. Transient absorption spectroscopy and photovoltaic measurements showed that the dyes keep their initial photoelectrochemical properties upon crosslinking. This bottom-up approach is certainly broadly applicable and opens the possibility to make "chemistry on the electrode" to functionalize and crosslink dyes with any component.